2017
DOI: 10.1261/rna.063800.117
|View full text |Cite
|
Sign up to set email alerts
|

Purine– and pyrimidine–triple-helix-forming oligonucleotides recognize qualitatively different target sites at the ribosomal DNA locus

Abstract: Triplexes are noncanonical DNA structures, which are functionally associated with regulation of gene expression through ncRNA targeting to chromatin. Based on the rules of Hoogsteen base-pairing, polypurine sequences of a duplex can potentially form triplex structures with single-stranded oligonucleotides. Prediction of triplex-forming sequences by bioinformatics analyses have revealed enrichment of potential triplex targeting sites (TTS) at regulatory elements, mainly in promoters and enhancers, suggesting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…To test this hypothesis, we used the En3 TTS that we applied to the nucleosome binding studies and analyzed its functional role in rDNA transcriptional regulation ( Figure 4G). The En3 TFO binds to the regulatory region of the rDNA transcription unit, and we recently showed that only the pyrimidine (Y-RNA_TFO) and not the purine (R-RNA_TFO) En3 TFO forms a stable triplex in vitro (Maldonado et al, 2018). Transfecting the TFO revealed a significant increase in the 47S pre-rRNA expression level with the pyrimidine TFO, whereas the purine TFO that does not bind to this site shows no effect ( Figure 4G).…”
Section: Triplex Stabilizing Nucleosomes Are Associated With Active Cmentioning
confidence: 89%
See 2 more Smart Citations
“…To test this hypothesis, we used the En3 TTS that we applied to the nucleosome binding studies and analyzed its functional role in rDNA transcriptional regulation ( Figure 4G). The En3 TFO binds to the regulatory region of the rDNA transcription unit, and we recently showed that only the pyrimidine (Y-RNA_TFO) and not the purine (R-RNA_TFO) En3 TFO forms a stable triplex in vitro (Maldonado et al, 2018). Transfecting the TFO revealed a significant increase in the 47S pre-rRNA expression level with the pyrimidine TFO, whereas the purine TFO that does not bind to this site shows no effect ( Figure 4G).…”
Section: Triplex Stabilizing Nucleosomes Are Associated With Active Cmentioning
confidence: 89%
“…To study the functional role of triplexes in chromatin, we used the triplex-forming motif En3 located in the enhancer of mouse rDNA that was previously characterized (Maldonado et al, 2018). Fluorescently labeled DNA templates of 200 bp harboring or lacking the En3 TTS were generated by PCR.…”
Section: Triplex Formation On Nucleosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that PAPAS interacts directly with the rDNA enhancer. The murine rDNA enhancer repeats are separated by T stretches of different lengths (Kuhn et al 1990;Maldonado et al 2018). Intriguingly, at active rRNA genes, these repeats wrap around UBF, which allows PAPAS to bind to the T stretches that separate individual enhancer repeats.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the resolution of the capture assay, we separated the rDNA promoter from the enhancer by digestion of genomic DNA with AccI and SalI, which cleave within the upstream terminator T 0 between the rDNA promoter and the enhancer elements (Grummt et al 1986). This experimental approach revealed that PAPAS comprising nucleotides −275/−336 captured the corresponding region in the rDNA enhancer that contains the TSS-proximal T stretch, termed En3-TFR (Maldonado et al 2018). RNA comprising PAPAS sequences from +5 to −55 did not capture significant amounts of rDNA (Fig.…”
Section: Papas Binds To the Rdna Enhancer Through A Stretch Of Homopumentioning
confidence: 97%